Using Guasha to treat musculoskeletal pain: A systematic review of controlled clinical trials - Choi Sun-Mi; Kim Jong-In; Choi Tae-Young; Lee Myeong Soo (BMC, 2010)
Abstract Background Guasha is a therapeutic method for pain management using tools to scrape or rub the surface of the body to relieve blood stagnation. This study aims to systematically review the controlled clinical trials on the effectiveness of using Guasha to treat musculoskeletal pain. Methods We searched 11 databases (without language restrictions): MEDLINE, Allied and Complementary Medicine (AMED), EMBASE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Korean Studies Information (KSI), DBPIA, Korea Institute of Science and Technology Information (KISTI), KoreaMed, Research Information Service System (RISS), China National Knowledge Infrastructure (CNKI) and the Cochrane Library. The search strategy was Guasha (OR scraping) AND pain. Risk of bias was assessed with the Cochrane criteria (i.e. sequence generation, blinding, incomplete outcome measures and allocation concealment). Results Five randomized controlled trials (RCTs) and two controlled clinical trials (CCTs) were included in the present study. Two RCTs compared Guasha with acupuncture in terms of effectiveness, while the other trials compared Guasha with no treatment (1 trial), acupuncture (4 trials), herbal injection (1 trial) and massage or electric current therapy (1 trial). While two RCTs suggested favorable effects of Guasha on pain reduction and response rate, the quality of these RCTs was poor. One CCT reported beneficial effects of Guasha on musculoskeletal pain but had low methodological quality. Conclusion Current evidence is insufficient to show that Guasha is effective in pain management. Further RCTs are warranted and methodological quality should be improved.